2020
DOI: 10.1093/humrep/deaa219
|View full text |Cite
|
Sign up to set email alerts
|

Donor oocyte recipients do not benefit from preimplantation genetic testing for aneuploidy to improve pregnancy outcomes

Abstract: STUDY QUESTION Do donor oocyte recipients benefit from preimplantation genetic testing for aneuploidy (PGT-A)? SUMMARY ANSWER PGT-A did not improve the likelihood of live birth for recipients of vitrified donor oocytes, but it did avoid embryo transfer in cycles with no euploid embryos. WHAT IS KNOWN ALREADY Relative to slow freeze, oocyte vitrification has l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 20 publications
2
13
0
Order By: Relevance
“…Despite the high success rates of OD cycles, some patients still perform PGT-A on their embryos as they feel it will increase their chances of getting pregnant and delivering a healthy baby. Previous paired cohort studies have shown that genetic testing in oocyte donor-recipient cycles is not associated with increased successful pregnancy and birth rates [7][8][9][10]. However, the results of these studies are exclusively based on cryopreserved OD [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the high success rates of OD cycles, some patients still perform PGT-A on their embryos as they feel it will increase their chances of getting pregnant and delivering a healthy baby. Previous paired cohort studies have shown that genetic testing in oocyte donor-recipient cycles is not associated with increased successful pregnancy and birth rates [7][8][9][10]. However, the results of these studies are exclusively based on cryopreserved OD [8].…”
Section: Introductionmentioning
confidence: 99%
“…Previous paired cohort studies have shown that genetic testing in oocyte donor-recipient cycles is not associated with increased successful pregnancy and birth rates [7][8][9][10]. However, the results of these studies are exclusively based on cryopreserved OD [8]. In Brazil and the rest of Latin America, OD cycles are usually performed using fresh oocytes.…”
Section: Introductionmentioning
confidence: 99%
“…In the only randomized trial using next-generation sequencing on trophectoderm biopsies, routine use of PGT-A did not improve reproductive outcomes; it did however increase ongoing pregnancy rate per embryo transfer in patients of advanced reproductive age (35-40 years) (Munne et al 2019). Accordingly, PGT-A is not the optimum embryo selection tool in younger patients (Doyle et al 2020) and scientific societies/expert opinions do not recommend the routine application of PGT-A in all IVF cycles (Practice and Genetic Counseling Professional Group of the American Society for Reproductive Medicine. Electronic address 2020; Chan, Ryu, and Zwingerman 2021;Dahdouh 2021;Gleicher, Patrizio, and Brivanlou 2021).…”
mentioning
confidence: 96%
“…The highest pregnancy and live birth rates from any IVF procedure have resulted from cycles utilizing donor oocytes. Due to the highly selective characteristics of donors to optimize the oocyte quality, some studies have shown a live birth rate as high as 50%-58% per transfer in donor oocyte cycles (2,3).…”
mentioning
confidence: 99%
“…The question of whether PGT-A in donor oocyte recipient cycles improves IVF outcomes has been debated in the literature. Some studies have argued that genetic testing might improve the IVF outcomes with embryos derived from donor oocyte cycles (5,6); conversely, other studies have revealed either the absence of clinical benefit (3,7) or even a negative impact on IVF outcomes (2). Although there is no clear consensus on the use of PGT-A for donor oocyte cycles, patients may inquire about its use, especially after failed cycles with untested embryos.…”
mentioning
confidence: 99%